A Review on Mechanical and Comfort Properties of Medical Bandages from Different Material and Finishing - Asmiza, Nur Athirah Nabilah; Nasir, Siti Hana (Progress in Engineering Application and Technology, 2021)
Textile materials and items designed to satisfy unique requirements are ideal for any surgical and medical use where a variety of endurance, durability, or sometimes moisture and permeability is needed. After a few hours of wearing bandage, they can become unstable, particularly when worn too loosely. Also, removing the bandages can be impossible since it can be stuck to the wound area. The smell they leave could be interpreted as infections, and some bandages can leave a stain in the injury area. In order to know what is the best materials for producing medical bandage that complies with mechanical and comfort properties, a review of the articles available need to be conducted. This research will determine the mechanical properties such as tensile strength and bursting strength, and comfort properties such as air permeability and thermal resistance. The variation in burst intensity represents the thickness of the fabric and the density of the region. Various characteristics of the fabric such as burst strength, compression extension and thickness, and weight, are essential aspects for the technology of various compression garments. On the other hand, the air permeability of the fabric relies on the thickness, density, also porosity of the fabric. Air permeability decreases at higher thickness and density and lower porosity. As a possible suggestion, the use of cotton and bamboo fibers to make bandages can be extended as both fibers are very good in mechanical and comfort features.